Large deflection analysis of frames by elements containing higher-order terms - Kien, Nguyen Dinh; Quang, Do Quoc (Vietnam Journal of Mechanics, 2003)
In this paper, the beam elements using higher-order terms for large deflection analysis of elastic frames are discussed. The elements based on the co-rotational method are derived using the strain energy and effective strains. The arc-length method is employed as numerical algorithm to compute the equilibrium paths. A number of numerical examples are studied to verify and compare the developed formulations. The obtained results show that while the inclusion of second-order local rotation contributes to some improvement in the accuracy, the higher-order axial strain hardly improves the numerical results. With the employment of the higher-order term elements, the accuracy in numerical analysis may be attained at coarser meshes.